Linux in easy steps - Mike Mcgrath (In easy steps., 2004)
This is an introduction to the use of the Linux operating system and some of the popular applications that are bundled with most Linux distributions. This book aims to be the perfect hand-holding guide for those who have some experience of the Windows operating system but now want to explore Linux for the first time.The book begins by relating the evolution of Linux and examines various popular distributions such as RedHat, Mandrake and SuSE. It advises how to prepare a computer so that Linux can be installed alongside a Windows operating system - this means that Linux need not replace the familiar Windows environment. Step-by-step instructions are provided to allow the reader to install Linux on their own computer. These include screenshots of each step together with clear explanations and useful tips.